Characterization of bullying in labor relations: a review of the literature - Jussara Luongo; Genival Fernandes de Freitas; Maria de Fátima Prado Fernandes (Universidad de Alicante, 2012)
The aim this paper is to reflect on the concepts and meanings attributed to bullying in labor relations in the context of the literature about this theme. Bullying is a phenomenon characterized by embarrassment, humiliation, constant and repeated violence. This situation can occur in different ways and times, however, labor relations bullying is more important because of the injury which can cause physical and psychological health of the worker, beyond the damage to the company as a result of injury to health its employee. Bullying at work, although in existence since the beginning of labor relations and hierarchical, it is still an issue that has recently been discussed and researched. Preventive measures against bullying are possibilities to curb its occurrence and ensure good relations in the workplace. Preventive measures for these outbreaks the desired effects are needed the direct intervention of companies in search of the organization's work environment and improving the organizational climate.